Fatal gambit - Lagercrantz, David (Lagercrantz, David. Rekke/Vargas deckare., 2024)
"Dead women should not show up in photos fourteen years beyond the grave... But if anyone is likely to recognize Claire Lidman, it's her husband, Samuel. He brings the photo to Hans Rekke and Micaela Vargas. Their initial skepticism gives way to cautious belief--but where will this case lead them? Meanwhile, Rekke's daughter, Julia, has a new boyfriend she's determined to keep secret. When word gets out, Micaela's world collapses around her, and Rekke is forced to confront a nemesis from his youth. Plunging us back into the political upheaval and financial crisis of the 1990s, as the Iron Curtain is finally lifted, the second Rekke and Vargas investigation sees our heroes grapple with a fiendish case that affects them both in profoundly personal ways"--